Bonaventura's "Nachtwachen" and Dostoevsky's "Notes from the Underground" A Comparison in Nihilism - Pribic, Rado (Slavistische Beitraege, 1974)
It ist the aim of this study to present a comparative point of view those aspects of nihilism which were detected in both novels, and to inquire into their roots, circumstances end effects.